2007
DOI: 10.1128/jcm.01502-06
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Disseminated Skin Lesions Due to Metarrhizium anisopliae in an Adult Patient with Acute Myelogenous Leukemia

Abstract: Metarrhizium anisopliae is a common insect pathogen that rarely causes infection in animals and humans. We report the first case of a disseminated skin infection in an immunocompromised adult patient. To date, only five cases of the disease in humans have been reported. There is no standard treatment for this infection. CASE REPORTA 62-year-old male presented in April 2005 with fever and malaise. Blood counts revealed pancytopenia with 330 neutrophils/l and 65% blasts. A bone marrow aspirate established a diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 12 publications
0
10
0
2
Order By: Relevance
“…The most frequently observed species in this group belonged to the genera Scedosporium and Fusarium. Also present were species that were rarely described previously as causing infectious diseases, such as Phomopsis longicolla, Metarhizium anisopliae (12), Arthrographis kalrae (13), and Bipolaris spicifera. Four cases of mixed infections were detected; two of those cases involved pediatric oncological patients from the same hospital (14), and the other cases involved an oncohematological patient and a subject addicted to alcohol.…”
mentioning
confidence: 89%
“…The most frequently observed species in this group belonged to the genera Scedosporium and Fusarium. Also present were species that were rarely described previously as causing infectious diseases, such as Phomopsis longicolla, Metarhizium anisopliae (12), Arthrographis kalrae (13), and Bipolaris spicifera. Four cases of mixed infections were detected; two of those cases involved pediatric oncological patients from the same hospital (14), and the other cases involved an oncohematological patient and a subject addicted to alcohol.…”
mentioning
confidence: 89%
“…Metarhizium anisopliae is a worldwide entomopathogenic deuteromycete that has been used for decades in programs of agricultural pest and disease‐vector control in various countries. Although M. anisopliae is not considered to be pathogenic for humans or domestic animals, starting in the late 1990s some rare cases of mycoses caused by the fungus in both immunocompromised and immunocompetent individuals have been reported (25). Gonzales and colleagues (26) compared the conidial photosensitization of two fungal species ( M. anisopliae and Aspergillus nidulans ) with MB and TBO under different incubation and light conditions.…”
Section: Photosensitizersmentioning
confidence: 99%
“…6,8 Two previous single case reports have suggested that topical natamycin is effective against M. anisopliae. 3,4 Systemic antifungals such as voriconazole may be an effective treatment for filamentous keratitis that is not responsive to topical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Eight cases of human infection by M. anisopliae have been previously reported, including 3 ocular infections. [3][4][5][6][7][8][9] An 18-year-old Columbian man with a painless round M. anisopliae corneal ulcer was cured with topical natamycin 5% and silver-sulfadiazine 1%. 3 A 36-year-old American female contact lens wearer with mild eye irritation attributable to a 2.5 mm round paracentral M. anisopliae corneal ulcer was left with a stromal scar after a 2-month course of topical medications including natamycin 5% and multiple antibacterials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation